COMPARISON OF ANTIPLATELET EFFICACY OF ORIGINAL AND GENERIC ENTEROSOLUBLE ACETYLSALICYLIC ACID IN PATIENTS WITH HIGH CARDIOVASCULAR RISK. SIMPLE BLIND CROSSED RANDOMIZED CONTROLLED STUDY (IKAR) - S. Yu. Martsevich; S. N. Tolpygina; E. S. Boychenko; R. E. Dubinskaya; Yu. V. Lukina; V. P. Voronina (Рациональная фармакотерапия в кардиологии)
Aim. To compare the antiplatelet efficacy of the original and generic enterosoluble tableted acetylsalicylic acid (ASA) in patients with high cardiovascular risk.Material and мethods. Patients (n=30) with high cardiovascular risk and indications for the ASA therapy were included in the study. Antiplatelet agents were withdrawn 3 weeks before study start (wash-out period). Study drugs were distributed at the start visit according to the randomization scheme. The first study drug course was 3 weeks, then next wash-out period lasting 3 weeks, and at last the second study drug course during 3 weeks occurred. Blood samples were taken; blood pressure and heart rate were recorded before and after therapies. ASA antiplatelet effect was evaluated by spontaneous and ADP-induced platelet aggregation assessment. Platelet aggregation was determined by the change turbidimetric translucent ability of the blood sample during the formation of aggregates after 2 minutes of exposure. ADP solution of three concentrations (0.5, 1 and 2 µMol) was used as an inductor of aggregation.Results. Significant differences between the compared drugs in effect on platelet aggregation, blood pressure and heart rate were not found. Signs of platelet desaggregation after 3 weeks of generic ASA therapy were found in 65, 34.5 and 31% of patients when aggregation was tested with ADP 0.5, 1 and 2 µMol respectively. Desaggregation was revealed in 65.4, 42.3 and 31% of patients treated with original ASA (p>0.05) in the same test and the same ADP inducing concentration.. Adverse events associated with study drugs were not registered.Conclusion. ASA generic Trombopol ® 75 mg (Pharmaceutical Factory Polpharma SA, Poland) and ASA original Aspirin® Cardio (Bayer AG, Germany) are equivalent in antiplatelet effect and tolerability.